Investigation of Tribolium castaneum resilin, a rubber-like insect cuticular protein - Li, Zhen (Kansas State University, 2013)
Resilin is a rubber-like cuticular protein found in many insect species. Resilin is important for jumping and flying of those insects due to the properties of high elasticity and efficient energy storage. Some recombinant proteins or peptides derived from resilin sequences have been synthesized to produce biomaterials that mimic the remarkable properties of resilin. This research focused on resilin in the red flour beetle, Tribolium castaneum. A cDNA for T. castaneum resilin was inserted into plasmid vectors for expression of resilin in Escherichia coli or Bacillus subtilus. Resilin produced in E. coli was used as antigen to produce a rabbit antiserum. Resilin synthesized by B. subtilis as a secreted protein was purified and used for biochemical studies. Resilin is highly expressed in the late pupal stage, and in hind wings, but not found in elytra of pharate adults, indicated by RT-PCR and immunoblot analysis. Recombinant resilin could be cross-linked in the presence of horseradish peroxidase and hydrogen peroxide, detected by appearance of a high molecular weight band on SDS-PAGE, which had blue fluorescence under ultraviolet light, presumably due to dityrosine linkages. RNA interference was used to knock down resilin expression in T. castaneum. Immunoblot and RT-PCR analyses indicated that resilin expression was successfully decreased by RNAi. However, the knockdown adults exhibited no apparent differences in morphology, behavior or life span from control beetles. Blue fluorescence under ultraviolet illumination has frequently been used as an indication of the presence of resilin containing dityrosine cross-links in insect tissues such as wings, wing tendons and leg joints. A similar blue fluorescence was observed in hind wings of T. castaneum. However, this fluorescence was not decreased in hind wings of beetles in which resilin expression was knocked down by RNA interference. There was a blue fluorescence in the hind wings of knockdown beetles, which was similar in distribution to that in wings of control insects. This result suggests that the observed blue fluorescence in T. castaneum hind wings is derived not only from cross-linked resilin but also from components other than resilin, perhaps other cuticular proteins that contain dityrosine cross-links.
Keywords: Resilin; Tribolium castaneum; Elastic protein; Cross-linking; Biochemistry (0487)